Effects of silica on mechanical and rheological properties of EPDM-based magnetorheological elastomers - Rusila Zamani, Abd Rashid; Norhasnidawani, Johari; Saiful Amri, Mazlan; Siti Aishah, Abdul Aziz; Nur Azmah, Nordin; Nurhazimah, Nazmi; S. N., Aqida; Mohd Aidy Faizal, Johari (IOP Publishing, 2021)
Magnetorheological elastomers (MREs) are a kind of emerged smart material, where its responsive moduli in terms of mechanical and rheological properties are largely influenced by the presence of an external magnetic field. However, the incompatibility on the surface properties of its raw materials (fillers and matrix) may deteriorate the required properties of MREs. Therefore, in this study, the innovation of MRE by embedding silica nanoparticles as an additive has been experimentally investigated to strengthen the interactions between filler and matrix, thus resulted in enhancement of mechanical and rheological properties of MRE. The ethylene propylene diene monomer (EPDM)-based MREs were fabricated by mixing the EPDM with carbonyl iron particles (CIPs) as the main filler and different contents of silica nanoparticles (0 wt%–11 wt%) as an additive. The microstructures, magnetic properties and tensile properties of isotropic EPDM-based MREs were observed by using field emission scanning electron microscopy, vibrating sample magnetometer and Instron Universal Testing Machine, respectively. Meanwhile, the rheological properties were examined under oscillatory loadings in the absence and presence of magnetic field using rotational rheometer. The experimental results showed that the silica nanoparticles play a significant role in improving the properties of EPDM-based MREs. The adhesiveness of silica into CIPs has amended the interfacial interactions between CIPs and matrix by occupying the gaps between distributed CIPs within the MRE. Consequently, the addition of 11 wt% silica has not only improved the tensile properties (tensile strength and elongation at break), but also enhanced the MR effect compared to EPDM-based MREs without silica. Thus, incorporation of silica nanoparticles as an additive in EPDM-based MRE has the potential to be further explored and compromised to bring new innovation in real engineering applications.